Case Report: A Case of Cystoid Macular Edema in Retinitis Pigmentosa With Central Retinal Vein Occlusion - Wang, Da-Hu; Gu, Cao; Yuan, Yuan-Zhi (Frontiers in Medicine, 2022)
Significance: Cystoid macular edema (CME) is a common complication of retinitis pigmentosa (RP). However, CME in RP with central retinal vein occlusion (CRVO) is rare. Prompt administration of anti-vascular endothelial growth factor (anti-VEGF) medication can achieve a satisfactory prognosis. Purpose: This report describes a case of using anti-VEGF medication to treat CME secondary to RP with impending or mild CRVO. Case Report: A 26-year-old femal presented for blurred vision in both eyes. Best-corrected visual acuity (BCVA) was 20/50 in the right eye and finger-counting in the left eye. According to ophthalmic examinations, CME secondary to RP in the right eye and CME secondary to RP with impending or mild CRVO in her left eye can be diagnosed. Central macular thickness (CMT) was 554 μm in the right eye and 831 μm in the left eye. Only the left eye was treated with a single intravitreal injection of anti-VEGF medication. One month later, BCVA increased to 20/200 and CMT decreased to 162 μm in the left eye. Interestingly, BCVA in the right eye also had a improvement (20/40) and intraretinal fluid decreased significantly. However, three months after injection, these improvements of both eyes were not maintained. Conclusion: This is the second case of RP with CRVO. Intravitreal injection of anti-VEGF medication for addressing CME secondary to RP with CRVO is an effective treatment, but it needs to be reinjected.